2008
DOI: 10.1186/ar2383
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in patients with rheumatoid arthritis: results from the QUEST-RA study

Abstract: IntroductionWe analyzed the prevalence of cardiovascular (CV) disease in patients with rheumatoid arthritis (RA) and its association with traditional CV risk factors, clinical features of RA, and the use of disease-modifying antirheumatic drugs (DMARDs) in a multinational cross-sectional cohort of nonselected consecutive outpatients with RA (The Questionnaires in Standard Monitoring of Patients with Rheumatoid Arthritis Program, or QUEST-RA) who were receiving regular clinical care.MethodsThe study involved a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
260
2
38

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 427 publications
(314 citation statements)
references
References 45 publications
14
260
2
38
Order By: Relevance
“…Life expectancy in RA patients (pts) is reduced by an average of 3 to 18 years in comparison with non RA population [1,2]. One of the most frequent causes of death is cardiovascular disease (CVD), due to the development of premature, accelerated atherosclerosis [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Life expectancy in RA patients (pts) is reduced by an average of 3 to 18 years in comparison with non RA population [1,2]. One of the most frequent causes of death is cardiovascular disease (CVD), due to the development of premature, accelerated atherosclerosis [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequent causes of death is cardiovascular disease (CVD), due to the development of premature, accelerated atherosclerosis [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Основной причиной преждевре-менной летальности при РА являются атеро-склероз и его осложнения [2]. Риск кардио-васкулярных катастроф высок не только при большей длительности РА, но и у молодых пациентов, серопозитивных по ревматоид-ному фактору (РФ), уже в первые годы забо-левания [3].…”
unclassified
“…Along with controlling traditional risk factors, there is compelling evidence that targeted therapies for controlling the effects of inflammation in RA may help to attenuate perioperative risk. Large registry studies, not specifically addressing the perioperative period, demonstrated tumor necrosis factor antagonist biologics, disease modifying anti-rheumatic drugs such as methotrexate and statins significantly lower cardiovascular risk [10,13,16].…”
Section: Discussionmentioning
confidence: 99%